Enantioselective synthesis of HIV protease inhibitor amprenavir via Co-catalyzed HKR of 2-(1-azido-2-phenylethyl)oxirane - Gadakh, Sunita K.; Reddy, R. Santhosh; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A short and efficient enantioselective synthesis of the HIV protease inhibitor amprenavir 1 (99% ee) as well as a formal synthesis of saquinavir 3 have been achieved in high enantiomeric purity starting from commercially available materials. Our strategy mainly comprises a Co-catalyzed two-stereocentred hydrolytic kinetic resolution (HKR) of racemic 2-(1-azido-2-phenylethyl)oxirane as the chirality inducing step. Also presented is a concise synthesis of (S)-3-hydroxytetrahydrofuran 4, the key structural feature, in high enantiomeric purity (98% ee). (c) 2012 Elsevier Ltd. All rights reserved.